A REVIEW OF THE GROUNDED THEORY APPROACH ON PUBLIC SERVICE INNOVATION IN INDIGENOUS VILLAGES - Sumarwanto Sumarwanto; Welly Kusuma Wardani; Asri Lestari; Taufik Maulana (DIA: Jurnal Administrasi Publik, 2026)
Public service innovation in traditional villages is a practice that not only reflects responses to community needs but also results from unique local cultural, social, and legal dynamics. This study aims to explore and understand the phenomenon of public service innovation in the context of traditional villages in Indonesia through a Constructivist Grounded Theory approach. This approach was chosen because it is capable of exploring the subjective meanings and interpretations of indigenous communities regarding the public services they experience. The research uses a qualitative method with literature review as the primary data collection technique, which includes an examination of scientific sources related to grounded theory, the authority of traditional villages, and public service innovation practices. The findings reveal that public service innovation in traditional villages cannot be separated from traditional values, local deliberation, and unique socio-cultural structures. Case studies such as the Majelis Krama Desa (MKD) in North Lombok and the recording of traditional marriages by the Malay Customary Institution in Muaro Jambi demonstrate how public services are implemented through customary mechanisms that still accommodate principles of human rights and national law. The study concludes that the Constructivist Grounded Theory approach provides a relevant framework for understanding public service innovation based on local wisdom in traditional villages, and recommends the importance of cultural sensitivity and participatory dialogue in the design and evaluation of public policies in traditional areas.